ETIKA MENGGUNAKAN SOSIAL MEDIA TIKTOK DALAM AJARAN ISLAM - Permana, Gumiwang Arkadia Putra; Kosasih, Aceng; Sari, Indah (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study aims to analyze the ethics of using the social media platform TikTok from an Islamic perspective. As a popular social media platform, TikTok has significantly changed the way individuals interact and share content. However, the use of TikTok also raises various ethical issues that need to be addressed, especially in the context of Islamic values. This research uses a qualitative approach with a literature review method to collect and analyze relevant literature. Data is collected from various sources, including books, journal articles, and official documents discussing ethics in social media usage and Islamic teachings. Content analysis techniques are used to identify the main themes that emerge from the literature and relate them to the context of TikTok usage. The results show that the ethics of using TikTok in Islamic teachings include principles such as maintaining the honor of oneself and others, avoiding indecent or harmful content, and promoting goodness and positive values. TikTok can be an effective tool for dawah and spreading Islamic values if used wisely and responsibly. This study provides in-depth insights into how Islamic teachings can be integrated into the use of TikTok, and its implications for character and moral development in the digital society. These findings are expected to serve as a reference for TikTok users, policymakers, and academics in understanding and applying ethical social media usage in accordance with Islamic teachings.